Improvement of Fifth Grade Students’ Mathematical Reasoning and Learning Activity with the Implementation of Problem Solving Learning Model - Efry Yenny; Ahmad Fauzan; Yanti Fitria (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2020)
This research is background by a low mathematical ability of students’ reasoning and learning activities in mathematics. Therefore, the aim of this research is to increase students’ reasoning and learning activities with the implementation of problem solving learning model. Type of research is classroom action research which have a cycle model consist of four components, namely planning, action, observation and reflection. This research conducted in two cycles that consisting of four meetings. At each cycle student activities during the learning process were observed, and at the end of each cycle a test of learning outcomes was given. The research is carried out with 30 fifth grade students from a public elementary school in semester 2 of the 2019/2020 school year. The instruments used were observation, and field notes, interviews and test results. The data obtained in the research were analyzed using qualitative analysis, analyzing the collection of data until all data has been collected. The data is reduced based on the problem under study, followed by the presentation of the data and finally the conclusion or verification. The results show that fifth grade students’ mathematicalreasoning and learning activities increase after the implementation of problem solving learning model.